TINGKAT KEKEBALAN AYAM PEDADING YANG DIBERI EKSTRAK BUAH MENGKUDU - Wiryati, Ida (E-Journal Widya Kesehatan dan Lingkungan, 2005)
The experiment was conducted to study the effect of Indian Mulberry fruit extract on immune response of broiler chiken using 160 day old chicks (DOC). The chiken were divided into four treatment groups with four replications of each ten DOC. Indian Mulberry unit fruit extract was given orally at dose levels of 0.1 g/kg BW (M1, 0.5 g/kg BW (M2), 1 g/kg BW (M3) and aquadest for the control group. Blood samples were collected for antibody titer, leucocyte and percentage of lymphocyte. Vaccination was done on day fourth and day twenty first. The data was analysed using Complete Randomized Design and Duncan method used for differences of mean treatments test. The result indicated that Indian Mulberry fruit extract significantly increased in antibody titer at dose level 0.5 g/kg BW. Percentage of lymphocyte on day fourteenth increased and then decreased while the treatment were stopped. Leucocyte were not significantly different by treatment.